(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article is devoted to the actual problem of the possibilities of using information and communication technologies in the process of teaching a foreign language. The author reveals the concept of mobile learning and considers its advantages in teaching foreign languages. The article provides a brief overview of mobile applications for teaching English and the experience of their use in the independent work of students.